2017
DOI: 10.1097/ncc.0000000000000396
|View full text |Cite
|
Sign up to set email alerts
|

A Prevalence Study of Psychosocial Distress in Adolescents and Young Adults With Cancer

Abstract: Findings suggest the need for evidence-based intervention strategies to enhance medical coping and social support in AYA cancer patients. Nurses are crucial to implementing psychological interventions in AYA cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 26 publications
1
35
1
Order By: Relevance
“…The reported prevalence of distress in cancer patients around the globe ranges from 22.1% to 89.1% [ 3 , 13 , 29 31 ]. In our study, the incidence of PD was 46.5%.…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of distress in cancer patients around the globe ranges from 22.1% to 89.1% [ 3 , 13 , 29 31 ]. In our study, the incidence of PD was 46.5%.…”
Section: Discussionmentioning
confidence: 99%
“…The intersection between AYAs’ dynamic developmental stage and the disruption associated with cancer creates unique psychosocial challenges [ 63 , 64 ], contributing to higher levels of psychological symptomatology [ 65 , 66 ] and supportive care needs [ 67 , 68 ], and poorer quality of life, coping and health outcomes [ 69 , 70 , 71 , 72 ]. Routine, regular and repeated screening and assessment of psychosocial issues and needs across the cancer trajectory allows for the timely identification of these concerns and the adjustment of care in response to changing needs, and it guides the provision of responsive and efficient services [ 63 , 64 , 73 ], but this depends on the availability of developmentally appropriate instruments [ 63 , 64 , 74 ].…”
Section: Psychosocial Carementioning
confidence: 99%
“…In the literature, the prevalence of distress among patients with cancer varies by country, cancer type, sex, age, and other sample characteristics. [21][22][23][24][25] Prior studies identi ed worry on the DT&PL as the most distressing, possibly as a surrogate for the intensity of distress. [26] McFarland et al reported that 40% of patients with breast cancer had fatigue, the most common physical problem associated with distress.…”
Section: Discussionmentioning
confidence: 99%